CAPSAICIN LOADED NANOLIPOSOME AGONIS TRPV1 : POTENSI TERAPI DALAM PENATALAKSANAAN ATEROSKLEROSIS - Gita Sastrawan, I Gede (Essential: Essence of Scientific Medical Journal; Vol 16 No 2 (2018): Volume 16 No. 2 (Juli-Desember) : Essence Of Scientific Medical Journal, 2019)
Introduction: Atherosclerosis known as the cause most of cardiovascular disease. Atherosclerosis is a complex pathological process that occurs in the blood vessel. This disease can be triggered by lipid modification, which cause chronic inflammation, eventually lead to thrombosis or stenosis. Result and Discussion: Capsaicin loaded nanoliposome was constructed by extracting capsaicin from chili (Capsicum frutescens L.) using Microwave Assisted Extraction (MAE) method. Then the capsaicin extraction results were constructed with nanoliposome using a thin film hydration method. Capsaicin has LD50 in male Swiss albino mice at 190 mg/kg per oral. Once administered orally, hydrophobic capsaicin will pass through the plasma membrane of endothelial cells and lead to the receptor side of the intracellular vanilloid-binding site reseptor TRPV1 (Transient Receptor Potential Vanilloid 1). The activated TRPV1 is capable of increasing the calcium ion influx which affect the increased expression of ATP-binding cassette transporter A1 (ABCA1) and the decreased expression of LRP1 (low-density lipoprotein protective protein 1). Due to increased Ca2+ influx, endothelial TRPV1 activation also increases PKA phosporilation (protein kinase A) which implies increased UCP2 expression resulting in decreased ROS formation and foam cell formation in atherosclerosis. Conclusion: Capsaicin loaded nanoliposome has potential in the management of atherosclerosis.